INVESTIGATING MOBILE TRAFFIC VIOLATION TICKETING SERVICE IN EGYPT: THE PROVIDER AND USER PERSPECTIVES - Abd El Aziz, Rasha (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
The advances in information and communication technology are affecting many aspects of the economy in developed and developing nations. The Internet and the World Wide Web innovations are increasingly promising to provide various tools to increase business and economic developmental processes for developing nations. Egypt in specific is one of the major countries in the region, especially with its very high population, around 94 million. This high population has in turn led to many challenges, on top of which is the transportation traffic, especially in the two main cities, Cairo and Alexandria. The Information and Communication Technology development in Egypt, together with the very high mobile adoption rate, reaching over 116% subscribers in a country with such a high population brings a calling need to adopt a mobile application as a partial solution to the traffic problem in Egypt. However, adopting a new technology is not primarily a technical problem but is rather a social problem, where customers acceptance plays an important role. Accordingly, a structured questionnaire will be designed in English and Translated to Arabic. Then, questionnaires will be distributed over a sufficient number of Egyptian car drivers. Also Semi-structured face to face interviews were selected with decision makers. Both questionnaires and interviews inquire on how do both parties perceive the current traffic and ticketing system in Egypt, and what are the main factors that affect the driver intention to adopt an m-traffic in Egypt. Data collected will be analyzed. Finally, conclusions will be drawn and recommendations will be proposed.